Indian resilience and rebuilding indigenous nations in the modern American west - Fixico, Donald Lee, 1951- (Modern American West, 2013)
"This illuminating and comprehensive analysis of Native nation's resilience in the twentieth century demonstrates how Native Americans reinvented themselves, rebuilt their nations, and ultimately became major forces in the United States. Written by Donald L. Fixico, Indian Resilience and Rebuilding, redefines how modern American history can and should be told"--Provided by publisher.